1997
DOI: 10.1002/(sici)1098-2396(199712)27:4<367::aid-syn10>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of mutant acetylcholine receptors in transgenic mice reduces the amplitude of neuromuscular synaptic currents

Abstract: While the slow onset of desensitization of nicotinic acetylcholine receptors (AChRs), relative to the rate of acetylcholine removal, excludes this kinetic state from shaping synaptic responses in normal neuromuscular transmission, its role in neuromuscular disorders has not been examined. The slow-channel congenital myasthenic syndrome (SCCMS) is a disorder caused by point mutations in the AChR subunit-encoding genes leading to kinetically abnormal (slow) channels, reduced miniature endplate current amplitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We investigated the basis for the reduction in MEPC amplitude in δS262T‐transgenic mice and showed that diminished MEPC amplitudes were not due to a decrease in ion channel conductance. Patch‐clamp recordings of single channels recorded from acutely dissociated muscle fibers of the flexor digitorum brevis demonstrated that AChRs of δS262T‐transgenic mice have a channel conductance of 61.8 pS, 21 which was identical to that of control end plate AChRs.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We investigated the basis for the reduction in MEPC amplitude in δS262T‐transgenic mice and showed that diminished MEPC amplitudes were not due to a decrease in ion channel conductance. Patch‐clamp recordings of single channels recorded from acutely dissociated muscle fibers of the flexor digitorum brevis demonstrated that AChRs of δS262T‐transgenic mice have a channel conductance of 61.8 pS, 21 which was identical to that of control end plate AChRs.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 2 is an electron micrograph of a neuromuscular junction from a forelimb muscle of a 6‐month‐old δS262T‐transgenic mouse, showing normal synaptic cleft, postsynaptic folds, and junctional sarcoplasm. 21…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, mutations in the neuronal nicotinic AChR in nocturnal frontal lobe epilepsy lead to a decrease in Ca 2+ permeability and overactive presynaptic terminals in inhibitory neurons (Kuryatov et al, 1997). Also in both the congenital slow-and fastchannel syndromes changes in the rates of desensitization are believed to be partially responsible for both impaired neuromuscular transmission and progressive muscle atrophy (Bhattacharyya et al, 1997;Milone et al, 1997;Sine et al, 1995). Finally, differences in the decay time of macroscopic postsynaptic currents observed in this syndrome may explain in part the dif-ferent levels of disease severity in SCS, presumably by through different degrees of cation overload.…”
Section: Introductionmentioning
confidence: 99%